Vitamin A deficiency during pregnancy of HIV infected and non-infected women in tropical settings of Northwest Ethiopia - Bekele Assegedech; Van Nhien Nguyen; Nakamori Masayo; Yitayaw Gashaw; Tegene Birhanemeskel; Huruy Kahsay; Kassu Afework; Mulu Andargachew; Wondimhun Yared; Yamamoto Shigeru; Ota Fusao (BMC, 2011)
Abstract Background Vitamin A deficiency (VAD) is known to be a major public health problem among women of reproductive age in South East Asia and Africa. In Ethiopia, there are no studies conducted on serum vitamin A status of HIV-infected pregnant women. Therefore, the present study was aimed at determining the level of serum vitamin A and VAD among pregnant women with and without HIV infection in tropical settings of Northwest Ethiopia. Methods In this cross-sectional study, blood samples were collected from 423 pregnant women and from 55 healthy volunteers who visited the University of Gondar Hospital. Serum concentration of vitamin A was measured by high performance liquid chromatography. Results After controlling for total serum protein, albumin and demographic variables, the mean ± SD serum vitamin A in HIV seropositive pregnant women (0.96 ± 0.42 μmol/L) was significantly lower than that in pregnant women without HIV infection (1.10 ± 0.45 μmol/L, P < 0.05). Likewise, the level of serum vitamin A in HIV seropositive non-pregnant women (0.74 ± 0.39) was significantly lower than that in HIV negative non-pregnant women (1.18 ± 0.59 μmol/L, P < 0.004). VAD (serum retinol < 0.7 μmol/L) was observed in 18.4% and 17.7% of HIV infected and uninfected pregnant women, respectively. Forty six percent of non-pregnant women with HIV infection had VAD while only 28% controls were deficient for vitamin A (P = 0.002). Conclusion The present study shows that VAD is a major public health problem among pregnant women in the tropical settings of Northwest Ethiopia. Considering the possible implications of VAD during pregnancy, we recommend multivitamin (which has a lower level of vitamin A) supplementation in the care and management of pregnant women with or without HIV infection.